Definition and Operationalization of Rural Territorial Development Concept in Costa Rican Sector Policy Instruments in the 2010s - Villalobos Jiménez, Alonso (2021)
The Costa Rican Law on the Transformation of the Agrarian Development Institute (IDA) into the Rural Development Institute (Inder) approved in 2012 has an explicit definition of Territorial Rural Development (TRD), which has been operationalized and reconfigured through Public Policy 2015-2030 for Costa Rican Rural Territorial Development and National Plan 2017-2022 for Rural Territorial Development. Results of the use of a content analysis technique of sequential questions subsumed in the definition of TRD and its disaggregation into elements covered in the public policy instruments, reveal that the interaction provided for by the Law between the economic and productive aspects of TRD, as well as between social aspects and the satisfaction of basic needs and the creation of opportunities, is maintained, while the institutional component is conceived of as a factor that enhances this relationship. This interaction takes on certain nuances during its operationalization which are discussed in this article. At the same time, the cultural component of the original definition practically disappears during the process of operationalization, while a previously unconsidered environmental component appears, which is largely based on the approach of natural resource management in rural regions.